ANALISIS KONVERSI LAHAN SAWAH DI PROPINSI JAWA TIMUR - Syarif Imam Hidayat (University of Jember, 2008)
The condition of switchover function of rice field farm per Regency / City in Provinsi of East Java pursuant to Result Podes 2006, that have been happened to by displace the function of farm rice field during 3 year ( 2003-2006) becoming agriculture farm of non rice field. This research conducted to know the conversion of farm rice field in East Java, inclusive of its spreading at regency and city and also time period of before autonomy era and after area autonomy, and also factors of what having an in with conversion of rice field. Research place selected by purposive sampling that is in Provinsi of East Java with the consideration that region of Provinsi of East Java have the farm of rice field which have potency to be downhill effect by industrial growth and the increasing of housing along with resident growth which fast enough. The analysis tools is use the analysis of trend linear with the smallest square method (Least Square Method) and simple linear regression analyse that its calculation by using computer program (soft ware) SPSS ( Statistical Program The For Social Science). Result of this research indicate that the wide growth of farm for the rice field of to have the downhill tendency, while wide growth of farm for the lawn of / building and page yard have the tendency mounting, and after the application of law about regency autonomy, the wide displace function of rice field farm become bigger than before the application into effect of autonomy at same period comparison (5 years series). The factor that influencing the conversion of rice field farm are variable the amount of the domestic housing, economic growth, and the amount of farmer. Keywords : Farming area, Conversion land